Syariah courts system in peninsular Malaysia - problems and suggested reforms / Wan Mansor Wan Mahmood - Wan Mahmood, Wan Mansor (Faculty of Law, 1987)
The scope of this project paper concerns the position of the Syariah courts system in Malaysia. It is the upmost important to discuss the situation of the Syariah courts because the establishment of the syariah courts reflect the status of Islam as being the Official Religion of Malaysia. This paper will also make an attempt to discover, that is to what extend has the Syariah courts succeeded in implementing the Islamic Law as conceived in the Al Quran and the Al Hadith, because as the situation stands now, the implementation of the Islamic Law is more inclined towards the modern legislation. In the second chapter, under the first heading, this paper will discussed the historical background of the Islamic Law before the arrival of the British. Under the second sub heading this paper will venture size to what extend has the British intervention succeeded in implementing the English Law to replace the Islamic Law which has been practical long before the British arrival.